Self-Medication with Antibiotics for Protection against COVID-19: The Role of Psychological Distress, Knowledge of, and Experiences with Antibiotics - Airong Zhang; Elizabeth V. Hobman; Paul De Barro; Asaesja Young; David J. Carter; Mitchell Byrne (MDPI AG, 2021)
Self-medication with antibiotics is a major contributing factor to antimicrobial resistance. Prior research examining factors associated with antibiotic self-medication has focused on an individual's knowledge about antibiotics, antibiotic usage practices, accessibility to antibiotic medication, and demographic characteristics. The role of psychological distress associated with perceived health risks in explaining antibiotic self-medication is less understood. This study was designed to address this knowledge gap in the context of the COVID-19 pandemic in Australia. An online survey of 2217 participants was conducted at the height of the initial outbreak and revealed that 19.5% of participants took antibiotics to protect themselves from COVID-19. Multivariate logistic analysis examined the predictors of taking antibiotics for protection against COVID-19. An integrative framework developed from the results illustrates potential pathways and facilitating factors that may contribute to prophylactic self-medication with antibiotics. Specifically, COVID-19 pandemic-induced psychological distress was significantly positively related to self-medication. Preventive use of antibiotics was also facilitated by a lack of understanding about antibiotics, inappropriate antibiotics usage practices, the nature of the patient-doctor relationship, and demographic characteristics. The findings highlight that to combat antimicrobial resistance due to self-medication, interventions need to focus on interrupting entrenched behavioural responses and addressing emotional responses to perceived health risks.